An Endoscopic Solution when the Gastric Tube is Twisted after an Esophagectomy (Global Journal of Medical Research, 2016)
Background and aims: The twisted gastric tube after an esophagectomy can be resolved with a minimally invasive treatment avoiding a reoperation. Methods: A 63 year old woman with tumor in the middle third of esophagus was operated on with esophagectomy and esophagogastric anastomosis in the neck. After 19days, she presented a funtional gastric tube estenosis secondary to rotation of the gastric tube. Results: A biodegradable stent was placed endoscopically and with interventional radiologist from the second portion of the duodenum to the prestenotic area of the gastric tube, fixed with clips. Conslusions: The biodegradable stent placement can be a possibility when a gastric tube volvulus occurs, avoiding a high risk reoperation.